Plant Structural Biology: Hormonal Regulations (Springer International Publishing, 2018)
After decades of dominance of genetics and genomics, the importance of structural biology is growing exponentially in the field of plant biology. The main objectives of this new book series is to "demystify" structural biology for plant researchers and to provide important insights into the basic molecular mechanisms underlying plant development through the diverse approaches utilized by structural biologists. The book series starts with a theme dedicated to hormonal signaling that has benefited from the application of structural biology. "Plant Structural Biology: Hormonal Regulations" provides up-to-date knowledge of the structural aspects of hormonal signal recognition, signal transduction, hormonal control of downstream regulatory pathways and hormonal crosstalk. The most distinctive features of this book as well as future titles is/will be to provide overview of cutting-edge research in the field of plant structural biology, and to serve as a compendium of various approaches that could be applied to problems being solved in modern plant biology. Last but not least, we hope this book will facilitate and broaden the community of (not only) plant scientists who are interested in structural biology approaches and tools. For these reasons, the style of this series is concise and general, in order to avoiding unnecessary details. Explanatory boxes describing the basics of specific approaches (e.g. X-ray crystallography, NMR, SAXS, molecular dynamics simulations, etc.) are included.